Anna Karenina and Others : Tolstoy's Labyrinth of Plots - Knapp, Liza (Book collections on Project MUSE., 2016)
With its complex structure, Anna Karenina places special demands on readers who must follow multiple plotlines and discern their hidden linkages. In her well-conceived and jargon-free analysis, Liza Knapp offers a fresh approach to understanding how the novel is constructed, how it creates patterns of meaning, and why it is much more than Tolstoy's version of an adultery story. Knapp provides a series of readings of Anna Karenina that draw on other works that were critical to Tolstoy's understanding of the interconnectedness of human lives. Among the texts she considers are The Scarlet Letter, a novel of adultery with a divided plot; Middlemarch, a multiplot novel with neighborly love as its ideal; and Blaise Pascal's Pensees, which fascinated Tolstoy during his own religious crisis. She concludes with a tour-de-force reading of Mrs. Dalloway that shows Virginia Woolf constructing this novel in response to Tolstoy's treatment of Anna Karenina and others.